2021
DOI: 10.1186/s13195-021-00886-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting progression and cognitive decline in amyloid-positive patients with Alzheimer’s disease

Abstract: Background In Alzheimer’s disease, amyloid- β (A β) peptides aggregate in the lowering CSF amyloid levels - a key pathological hallmark of the disease. However, lowered CSF amyloid levels may also be present in cognitively unimpaired elderly individuals. Therefore, it is of great value to explain the variance in disease progression among patients with A β pathology. Methods A cohort of n=2293 participants, of whom n=749 were A β positive, was selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Studies in non-human primates additionally validated these findings in conscious, untreated, and MPTP-treated animals [69,70]. 18 F-BCPP-EF is currently under investigation for the assessment of patients with NDs. In PD patients, decreased binding levels of 18 F-BCPP-EF have been observed in several neuroanatomical key structures without reaching statistical significance [71].…”
Section: Quantitative Assessment Of Mitochondrial Complex I By Positr...mentioning
confidence: 82%
See 4 more Smart Citations
“…Studies in non-human primates additionally validated these findings in conscious, untreated, and MPTP-treated animals [69,70]. 18 F-BCPP-EF is currently under investigation for the assessment of patients with NDs. In PD patients, decreased binding levels of 18 F-BCPP-EF have been observed in several neuroanatomical key structures without reaching statistical significance [71].…”
Section: Quantitative Assessment Of Mitochondrial Complex I By Positr...mentioning
confidence: 82%
“…In the same study, the longitudinal assessment of PD patients showed a trend without reaching the significance level [71]. In a multimodal PET imaging study in patients with AD, 18 F-BCPP-EF binding is closely associated with the in vivo tau deposition but not the overall amyloid load [72]. 18 F-BCPP-EF yields immense promises for evaluating mitochondrial dysfunction in patients with NDs.…”
Section: Quantitative Assessment Of Mitochondrial Complex I By Positr...mentioning
confidence: 90%
See 3 more Smart Citations